18F-Fluorodeoxyglucose positron emission tomography computed tomography detection of single organ vasculitis of the breast: A case report. Issue 12 (26th March 2021) - Harada, Taku; Sasaki, Yosuke; Tokunaga, Takahiro; Yoshizawa, Ayuha; Miura, Sakiko; Ikeda, Keiichiro; Saito, Tsukasa; Hiroshige, Juichi
Abstract: Rationale: Although single organ vasculitis (SOV) is a rare occurrence and it is difficult to diagnose, its possibility as a cause of fever of unknown origin (FUO) must be considered. Recently, the usefulness of 18F-fluorodeoxyglucose positron emission tomography computed tomography (FDG PET/CT) in the diagnosis of unknown fevers due to vasculitis, especially in cases of small and medium-sized vasculitis, has begun to be pointed out. Patient concerns: We report the case of an 84-year-old woman with persisting fever for more than 2 weeks. She had no accompanying symptoms, other than fever, and the physical examination, echocardiography, and contrast-enhanced CT did not reveal any diagnostic clue. Diagnoses: The FDG PET/CT revealed positive uptakes of FDG in the left breast, with a standardized uptake value (SUV) of 2.9. The biopsy specimen of the left breast lesion revealed rupture of the elastic plate and evidence of fibrinoid necrosis of arteries, leading to the diagnosis of polyarteritis (PAN). Further angiographic examination and additional imaging did not reveal the presence of other lesions. Therefore, the diagnosis was established as a PAN-SOV of the left breast. Interventions: This patient has improved with follow-up only. Outcomes: There has been no evidence of a relapse of PAN over a 5-year follow-up period. Lessons: SOV presenting with unspecific local symptoms is difficult to diagnose based on the medical history and clinical examination. Our findings show that early "Combination of PET-CT and biopsy" can be a powerful diagnostic tool in patients with FUO for whom diagnosis of the underlying cause is difficult despite appropriate clinical examination.